Proton transfer mechanism of 1, 3, 5-tri(2-benzimidazolyl) benzene with a unique triple-stranded hydrogen bond network as studied by DFT-MD simulations. (1st December 2015) - Nimmanpipug, Piyarat; Laosombat, Teerawit; Sanghiran Lee, Vannajan; Vannarat, Sornthep; Chirachanchai, Suwabun; Yana, Janchai; Tashiro, Kohji
Abstract: Clarification of proton transfer mechanisms is crucial to the development of proton exchange membrane fuel cells (PEMFCs). Nitrogen-containing heterocyclic compounds ( e.g., imidazole derivatives) are well known for their potential to assist proton hopping through hydrogen bond networks at high temperatures. Among the many imidazole derivatives reported thus far, 1, 3, 5-tri(2-benzimidazolyl)benzene (TBIB) is assumed to be one of the most promising imidazole derivatives because of its triple-stranded three-dimensional hydrogen bond network. In fact, TBIB immersed into a polyphosphoric acid matrix was reported to enhance the proton conductivity to 10 −2 –10 −1  S/cm in the high-temperature range up to 170 °C. In the present work, the proton transfer mechanism has been investigated using density functional theory (DFT) with a DNP basis set and the GGA exchange-correlation functional BLYP and molecular dynamics simulations (MD) to provide insight into the cause of the remarkable proton conductivity of TBIB. Transition states in the proton hopping process were obtained using two types of models constructed from the X-ray crystal structure: an isolated two-molecule system (type I) and a periodic three-molecule system (type II). Alterations of charge distribution, molecular conformation and molecular orientation were investigated from these models. Further, the diffusion coefficient of proton transfer has been estimated and the mechanisms along three specific channels that favor efficient proton transfer between the layers have been examined in detail. Additionally, the effect of an electric field perturbation was investigated for these two models. The application of an external electric field was found to affect the proton hopping process remarkably, as evidenced by large changes in the activation energies and proton hopping times. In conclusion, the highly organized hydrogen-bonding network observed for TBIB was found to be a key factor in enhancing the efficiency of proton transfer. Highlights: Proton transfer in a benzimidazole derivative with a unique packing was simulated. Partial charge alteration due to electric field perturbation was elucidated. Proton hopping mechanism related with hydrogen bond network was suggested